2022
DOI: 10.1088/1361-6463/ac791c
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental evidence of the cathode erosion in a plasma spray torch

Abstract: The lifetime of tungsten cathodes used in plasma spray torches is limited by processes leading to a loss of cathode material. It was reported in the literature that the mechanism of their erosion is the evaporation. A model of the ionization layer of a cathode is developed to study the diffusive transport of evaporated tungsten atoms and tungsten ions produced due to ionization by electron impact in a background argon plasma. It is shown that the Stefan-Maxwell equations do not reduce to Fick law as one could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The properties obtained allow estimation of the lifetime and efficiency of plasma accelerators using tungsten cathode and Ar as driving medium. Baeva et al [49] established a cathode ionosphere model to investigate the diffusion transport of evaporated tungsten atoms and tungsten ions due to electron shock ionization in Ar plasma. The results exhibited that the Stefan-Maxwell equation was not reduced to Fick law due to significant diffusion velocities of Ar ions.…”
Section: Hsu Et Al 1983 2dmentioning
confidence: 99%
“…The properties obtained allow estimation of the lifetime and efficiency of plasma accelerators using tungsten cathode and Ar as driving medium. Baeva et al [49] established a cathode ionosphere model to investigate the diffusion transport of evaporated tungsten atoms and tungsten ions due to electron shock ionization in Ar plasma. The results exhibited that the Stefan-Maxwell equation was not reduced to Fick law due to significant diffusion velocities of Ar ions.…”
Section: Hsu Et Al 1983 2dmentioning
confidence: 99%
“…A large number of numerical modelings [22,[26][27][28][29] and experimental studies [30][31][32][33][34] have been performed to analyze the mechanisms of anode erosion, and propose the methods to inhibit the anode erosion. The modeling found that the arc usually attached on the anode surface in the diffusive or constricted forms.…”
Section: Introductionmentioning
confidence: 99%
“…The unified modeling approach has been successfully applied for axially symmetric modeling of low-current arc discharges [10][11][12][13][14][15]. Unfortunately, the approach is highly computationally intense for high values of the current density, and therefore its applications to high-current arcs are limited to one dimension in space; see citations in section 3.1 of [4] and [5,6,[16][17][18][19][20][21] as further references. The arc-electrode interaction in geometries of practical interest is a multidimensional phenomenon.…”
Section: Introductionmentioning
confidence: 99%